2023
DOI: 10.3390/foods12112162
|View full text |Cite
|
Sign up to set email alerts
|

Edible Insects in Thailand: An Overview of Status, Properties, Processing, and Utilization in the Food Industry

Abstract: Edible insects have become increasingly popular in Thailand as a nutritious and appealing alternative food source. As the edible insect industry in the country expands rapidly, efforts are being made to transform it into an economically viable sector with substantial commercial potential. Some of the most consumed and sold edible insects in Thailand include locusts, palm weevils, silkworm pupae, bamboo caterpillars, crickets, red ants, and giant water bugs. With its strong growth, Thailand has the potential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Furthermore, In Thailand the application of Good Agricultural Practices (GAP) especially in cricket faming, mark a crucial milestone for advancing the insect farming industry and accessing global markets (Krongdang et al, 2023). The edible insects' market in Thailand also emphasizes both importing and exporting flows which highlight the productivity of the edible insects.…”
Section: Edible Insects' Farmingmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, In Thailand the application of Good Agricultural Practices (GAP) especially in cricket faming, mark a crucial milestone for advancing the insect farming industry and accessing global markets (Krongdang et al, 2023). The edible insects' market in Thailand also emphasizes both importing and exporting flows which highlight the productivity of the edible insects.…”
Section: Edible Insects' Farmingmentioning
confidence: 99%
“…The edible insects' market in Thailand also emphasizes both importing and exporting flows which highlight the productivity of the edible insects. For instance, between the year 2014-2022, certain edible insects namely crickets, grasshoppers, and bamboo caterpillars were traded internationally which imports to China and Myanmar exceeded US $800,000, whereas exports to the United States, Japan, and England totaled over US $200,000 in 2022 (Krongdang et al, 2023). Gahukar (2016) demonstrated that Thailand's silkworm farming involves 137,000 households which responsible for 80% of the country's total silkworm production.…”
Section: Edible Insects' Farmingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely known that edible insects are characterized by high nutritional value, influenced by their high protein content [ 1 , 2 ]. In addition, insects are a good source of vitamins (A, B 6 , and B 12 ) and minerals (Fe, Ca, Zn, and Se) [ 2 , 3 ]. They can, therefore, serve as an alternative to traditional protein sources, especially meat [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%